Microbeam-coupled capillary electrophoresis - Garty, G. (Radiat Prot Dosimetry, 2015)
Within the first few microseconds following a charged particle traversal of a cell, numerous oxygen and nitrogen radicals are formed along the track. Presented here is a method, using capillary electrophoresis, for simultaneous measurement, within an individual cell, of specific reactive oxygen species, such as the superoxide radical ([Formula: see text]) as well as the native and oxidised forms of glutathione, an ubiquitous anti-oxidant that assists the cell in coping with these species. Preliminary data are presented as well as plans for integrating this system into the charged particle microbeam at Columbia University.